SWOT analysis Investigating children and youth in the Inquiry official: วิเคราะห์ SWOT การสอบสวนเด็กและเยาวชนในชั้นพนักงานสอบสวน - Khundiloknattawasa, Suwanna (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
The purpose of this research was to analyze Strengths Weaknesses Opportunities Obstacles Investigating children and youth in the Inquiry official. Data were collected through in-depth interviews with 95investigating personnel specialized in children and youth and content analysis. The results of the research revealed that 1) The strengths emphasize that the investigative officers who are patriotic possessing knowledge and experience in the investigation. 2) Weaknesses, inexperienced investigators reluctantly appointed and lack of specialized expertise. 3) Opportunities for children and youth, the government attaches importance to this issue have specific laws and agencies involved. and 4) Threats arise from the geographical features of each province that are obstacles in the investigation of children and youth. There are not enough personnel involved to provide protection for children and youth. In particular, the agency responsible for children and youth of the Royal Thai Police is unclear and serious in resolving the problem. There is still no mechanism for driving. After that, the information obtained was formulated as a strategy for the development of juvenile investigations. In order to develop investigative officers to be effective in conducting investigations, 4 strategies are as follows: 1) Developing the potential of investigative officers to be professional. 2) Developing investigative systems relating to children and youth. 3) Recruitment and appointment Personnel to act as investigating officers and 4) Creating morale.